RNA-sequencing analysis of gene expression in a rat model of acute right heart failure - Yunshan Cao; Yahong Li; Mianmian Wu; Jiyang Song; Min Zhang; Yichao Duan; Kaiyu Jiang; Xing Zhou; Yan Zhang (Pulmonary Circulation, 2020)
Background: Acute right heart failure (RHF) is the main cause of death in patients with acute pulmonary embolism and emergent pulmonary hypertension. However, the molecular mechanisms underpinning the acute RHF and the interactions between the right (RV) and left ventricles (LVs) under the diseased condition remain unknown. Methods and results: The Sprague Dawley male rats were randomly divided into the normal control, sham, and pulmonary artery banding (PAB) groups. One hour after the PAB operation, after measuring the haemodynamic and anatomical parameters, the free walls of RV and LV were harvested to detect the differential gene expression profiling by high-throughput RNA sequencing. The results showed that the PAB lead to 50–60% obstruction of the main pulmonary artery, which was accompanied by the significant elevation in the positive rate of rise in RV pressure and the maximum RV pressure as compared to the sham group. Moreover, compared with the counterparts in the sham group, the RV and LV in the PAB group exhibited 2057 differentially expressed genes (DEGs, 1159 upregulated and 898 downregulated) and 1196 DEGs (709 upregulated and 487 downregulated), respectively (DEG criteria: |log 2 fold change| ≥1, q value ≤0.05). In comparison to the sham group, the enriched pathways in the PAB group include nuclear factor-κB signalling pathway, extracellular matrix–receptor interaction, and nucleotide oligomerization domain-like receptor signalling pathway. Conclusions: The PAB rat model exhibited the haemodynamic and gene expression changes in the RV that lead to acute RHF. Further, the acute RHF induced by pressure overload also caused gene expression changes in the LV, suggesting the molecular interactions between the RV and LV under the diseased condition.